2013
DOI: 10.1177/039463201302600332
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Including Serratiopeptidase Improves Outcomes of Mechanical-Antibiotic Treatment of Periimplantitis

Abstract: This study was designed as a retrospective analysis of clinical outcomes of cases of periimplantitis treated by mechanical debridement and the administration of antibiotics combined or not with the administration of either the proteolytic enzyme serratiopeptidase (SPEP) or non-steroidal anti-inflammatory drugs (NSAIDs). Clinical charts of 544 partially edentulous patients treated for periimplantitis between June 1996 and December 2010 were analyzed to obtain clinical data of the affected implants just before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Measurement was re -calculate as following: %recovery = (post -operative measurement −preoperative measurement) /preoperative measurement × 100% has shown positive results in inflammatory disorders around teeth and dental implants [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement was re -calculate as following: %recovery = (post -operative measurement −preoperative measurement) /preoperative measurement × 100% has shown positive results in inflammatory disorders around teeth and dental implants [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that serratiopeptidase enhanced the efficacy of antibiotics by increasing tissue concentration of the antibiotics [ 56 , 57 ]. A retrospective study in 544 patients was conducted by [ 58 ] on partially edentulous patients treated for peri-implantitis by evaluating clinical charts. The study indicated that serratiopeptidase helps in the repair of bone lesions and speeds up the clinical healing process.…”
Section: Application Of Serratiopeptidase In Therapeuticsmentioning
confidence: 99%
“…Subsequently, this bio lm can instigate bone loss. The management of peri-implantitis entails employing a combination of mechanical techniques, such as the utilization of carbon ber curettes to eliminate the bio lm, and chemical interventions aimed at eradicating bacteria through disinfection treatments and antibiotic administration [5][6][7]. Recently, various efforts have been undertaken to prevent peri-implantitis by exploring the application of antibacterial substances to treat the implant surfaces, thereby mitigating the risk of infection [8].…”
Section: Introductionmentioning
confidence: 99%